Corporate citizenship as stakeholder management: An ordonomic approach to business ethics - Ingo Pies; Stefan Hielscher; Markus Beckmann (Martin-Luther-Universität Halle-Wittenberg, Lehrstuhl für Wirtschaftsethik, 2008)
This paper argues that the perspective of ordonomic—a rational-choice based analysis of (interdependencies between) social structure and semantics—can provide new insights into the changing role of business in society. We claim (a) that the proper role of business is societal value creation, (b) that business firms—as economic players— can take on the role of improving the rules of the game, i.e., act as corporate citizens, and (c) that business ethics can and should provide theoretical guidance for “corporate citizenship” and the political processes of “new governance,” in which business firms, together with civil society organizations and state actors, work together to solve problems, especially at an international (and sometimes even global) scale. Finally, we show (d) that this perspective requires overcoming two blind spots in recent discourse about the appropriate analytical foundations of business ethics.
urn:nbn:de:gbv:3:2-7507
Keywords: A12; A13; D02; D63; M14; 330; business ethics; corporate citizenship; corporate social responsibility; new governance; ordonomics; rational choice; social dilemmas; stakeholder theory